2008
DOI: 10.1128/cvi.00254-07
|View full text |Cite
|
Sign up to set email alerts
|

A Neutralizing Antibody to the A Chain of Abrin Inhibits Abrin Toxicity both In Vitro and In Vivo

Abstract: Plant ribosome-inactivating proteins (RIPs) are RNA N-glycosidases that inhibit protein synthesis in cells. Abrin, a type II RIP, is an AB type toxin, which is one of the most lethal types of toxin known. The B chain facilitates the entry of the molecule into the cell, whereas the A chain exerts the toxic effect. We have generated hybridomas secreting antibodies of the immunoglobulin G class specific to the recombinant A chain of abrin. One monoclonal antibody, namely, D6F10, rescued cells from abrin toxicity.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
34
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 38 publications
2
34
0
Order By: Relevance
“…In one study, phage display technology was utilized to select anti-abrin human monoclonal antibodies from a human naïve scFv library (Zhou et al, 2007), however these were not examined in animal models for their therapeutic value. In another study, a monoclonal antibody mapped to abrin A-chain, was found to protect mice from abrin challenge when given 1 h prior to exposure (Surendranath and Karande, 2008).…”
Section: Introductionmentioning
confidence: 97%
“…In one study, phage display technology was utilized to select anti-abrin human monoclonal antibodies from a human naïve scFv library (Zhou et al, 2007), however these were not examined in animal models for their therapeutic value. In another study, a monoclonal antibody mapped to abrin A-chain, was found to protect mice from abrin challenge when given 1 h prior to exposure (Surendranath and Karande, 2008).…”
Section: Introductionmentioning
confidence: 97%
“…[9][10][11][12] The only known neutralizing monoclonal antibody (mAb) namely D6F10 for abrin was reported from our laboratory. 13 This mAb was found to inhibit the enzymatic activity of the abrin A chain in vitro and also conferred protection to mice in vivo. 13,14 Toward mapping the epitope corresponding to this mAb, at first various overlapping truncated forms of the abrin A chain were constructed and examined for binding to the mAb.…”
Section: Introductionmentioning
confidence: 98%
“…13 This mAb was found to inhibit the enzymatic activity of the abrin A chain in vitro and also conferred protection to mice in vivo. 13,14 Toward mapping the epitope corresponding to this mAb, at first various overlapping truncated forms of the abrin A chain were constructed and examined for binding to the mAb. We could conclude that the epitope lay in the amino acids 1-123 of ABA.…”
Section: Introductionmentioning
confidence: 98%
“…AT shows significant similarities to ricin toxin (RT) at the sequence level as well as the structural level, but it is 75 times more toxic than the latter (the estimated LD 50 of AT in mice is 0.04 mg/kg of body weight, and the LD 50 of RT is 3 mg/kg). 2 In addition, AT can be extracted using a relatively simple and cheap procedure. These characteristics make AT a choice for a suitable assassination weapon or a biological warfare agent .…”
Section: Introductionmentioning
confidence: 99%
“…3 Toxin poisoning usually can be prevented by vaccination with toxoid, 4,5 or by passive administration with antibodies in experimental animals. 2,6 Both procedures are effective in the prophylaxis or therapy of toxin poisoning in mice. Currently, only vaccines based on a toxoid of AT ( attenuated with formalin as reported by Griffiths 5 ) and A chain subunit ( ATA mutant 1 and truncated ATA 7 ) produced in our lab, were effective in neutralizing intoxication by AT.…”
Section: Introductionmentioning
confidence: 99%